A review of DNA methylation in depression. (September 2017) - Chen, Dongmei; Meng, Lin; Pei, Fei; Zheng, Yang; Leng, Jiyan
Highlights: BDNF and NR3C1 gene methylation levels were correlated with depression. The connection of SLC6A4 and depression was conflicting. The epigenetic changes effect on depression. Abstract: As one of the most common psychiatric disorders, depression has been a major public health problem. Growing evidence suggests that epigenetic modification is essential in biological processes of depression. Recently, DNA methylation has been regarded as a potential link between environment and depression. In this review, we reviewed current studies of the association between DNA methylation and depression. The association between DNA methylation of seven genes, including BDNF, SLC6A4, NR3C1, 5-HTR ( 1A, 2A, and 3A ), FKBP5, MAO - A and OXTR, and depression were reviewed in this study. Most studies showed BDNF and NR3C1 gene methylation levels were correlated with depression while the connection of SLC6A4 and depression was conflicting. Although evidence provided insights to epigenetic processes in depression, the findings were inconsistent. Therefore, longitudinal studies in animal models and in patients with depression are needed to further investigate the diagnostic predictive value of DNA methylation reliably.